Beauveria bassiana Growth and Development in Various Liquid Media (Biosaintifika: Journal of Biology & Biology Education, 2022)
Beauveria bassiana is entomopathogenic fungi that can be cultivated on solid or liquid media. The cultivation of B. bassiana on cracked corn medium leaves unwanted waste. Therefore, cultivating B. bassiana on liquid media is expected to shorten the cultivation time and leave no waste. The purpose of the research was to analyze the physical characteristics of the B. bassiana colony, nutritional changes of the liquid media, and  the pH level changes of the liquid media. This research used an experimental complete randomized design with six treatments and 4 times repetitions. The main phases of this research were the subculture of B. bassiana isolate; the preparation of liquid media consisting of distilled water, Potato Dextrose Broth (PDB), Potato Sugar extract  (PSE), PSE+NPK 1%, PSE+coconut water, PSE+NPK 1%+coconut water each for 150 ml; B. bassisana inoculation into the liquid media; incubation process for 30 days; and measurement of fungal blastospore density, medium pH, and carbohydrate, protein, and lipid content. The results obtained from the morphological observation of B.bassiana on liquid media showed that the colonies are white, growing on the surface of the media with a powdery texture. There are some differences in the nutrient content of the media after 30 days of B. Bassiana incubation. After the incubation, there is an increase in carbohydrates and a decrease in protein and lipid content, as well as an increase in the pH level of the media.